Efficiently Secure Data Communications Based on CBC-RC6 and the Overflow Field of Timestamp Option in an IPv4 Packet - Awadh, Wid Akeel; Hashim, Ali Salah; Hamoud, Alaa Khalaf (Informatica, 2022)
In recent times, many researchers have directed their research efforts towards increasing the privacy and security requirements in the wireless communication networks area. The reason for this is the inappropriateness of using traditional security processes for reliable, efficient, and robust communication over networks that are not secured. Thus, this study contributes to the enhancement of security in wireless communication networks by proposing the use of steganography combined with cryptography so that secret information can be sent using IPv4 as cover to conceal secret messages, thereby, securing the messages. Steganography is described as the process of concealing secret data in a way that it cannot be traced by an intruder. Here, the intruder is unable to detect any modifications made to the original media. Meanwhile, cryptography is referred to as the process through which plain text can be converted into ciphertext to enable the transmission of data through certain channels of communication in a format that cannot be read by a normal user. Network Steganography is a mechanism that involves the use of protocols for communication that control the path of the channel via the network. Initially, the TCP/IP protocols have been a good candidate for network steganography, due to the many benefits that can be derived from its use. One of such benefits is that allows the creation of a variety of concealed channels that can be used for secret communication. In order to enable communication over the network, the use of Cryptographically Secure Pseudo-Random Number Generator (CSPRNG) is employed in the proposed system so that the encryption/decryption key can be generated. The initial step in our study involves encrypting the secret data that needs to be protected, and this is achieved through the use of the CBC-RC6 cryptographic algorithm. After the encryption has been successfully performed, a covert channel is created for the encrypted data through the use of the Overflow field of the Timestamp option of IPv4. With this method, debugging and measurement over networks is carried out using the timestamp option, and the aim of this is to build storage-based network steganography. One of the strategies used in this work to deter the possible detection of covert communication is the deployment of legal overflow data.